간호학생을 위한 국제보건역량강화 프로그램의 개발 및 효과 - 황선영; 김진선; 안현미; 강선주; Hwang, Seon Young; Kim, Jin Sun; Ahn, Hyunmi; Kang, Sun Joo (지역사회간호학회지, 2015)
Purpose: This study developed a short-term education program aiming to strengthen global health capacity in nursing students, and examined the effects of the program. Methods: The subjects of this study were 83 students recruited from 29 nursing colleges. Domestic workshops and overseas training in the Philippines were offered. For data collection and analysis, the triangulation method was adopted. Results: Students' critical thinking disposition and global leadership capacity were significantly increased. Thematic content analysis derived fifteen themes: expansion of global health, understanding of cultural diversity, vision of being a global leader, cultivation of communication skills, open mind toward people with different culture, pride and vocation, understanding of nursing in foreign countries, understanding of visiting nurse service, sustainability, understanding of local needs and environments, and education methods with an emphasis on participants, broader view and thinking of the world, reflection on the characteristics of a nurse, development through cooperation, and development through programs. Conclusion: The global health capacity building program improved nursing students' view of global health and nursing care. It is needed to develop continuously diverse global health capacity-building programs for nursing students.